An unusual presentation of branchial cyst mimicking carotid body tumor - C., Tharun Ganapathy; Suresh, Abinayaah; P., Manimaran (International Surgery Journal, 2017)
Branchial cleft anomalies are a common cause of lateral neck masses and may present with infection, cyst enlargement or fistulae. Abscesses and necrotic adenopathy can also be difficult to distinguish from a branchial cyst, particularly if it has previously been infected. Here we report an unusual presentation, a case of a branchial cleft cyst in a 19-year old girl completely encasing the carotid bifurcation and encircling the hypoglossal nerve mimicking a carotid body tumour